2023
DOI: 10.3390/antiox12071438
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Salicylic Acid and Proline Mitigates Drought Stress in Rice (Oryza sativa L.) through the Modulation of Physiological Attributes and Antioxidant Enzymes

Tahmina Akter Urmi,
Md. Moshiul Islam,
Kamrun Naher Zumur
et al.

Abstract: Salicylic acid (SA) and proline exhibit protective effects against a wide range of stresses. However, the combined impact of SA and proline on rice under drought stress is still unknown. Therefore, we investigated the protective roles of SA and/or proline in conferring drought tolerance in rice. There were eight treatments comprising the control (T1; 95–100% FC), 1.5 mM SA (T2), 2 mM proline (T3), 0.75 mM SA + 1 mM proline (T4), 45–50% FC (T5, drought stress), T5 + 1.5 mM SA (T6), T5 + 2 mM proline (T7), and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 90 publications
0
1
1
Order By: Relevance
“…In the present study, activities of antioxidant enzymes such as CAT, SOD, and POD decreased under stress in both mungbean lines, but reports depict that up or down-regulation activities of antioxidant enzymes or plant genotype-specific and stress type-specific ( Wang et al, 2012 ; Rai, Morales & Aphalo, 2021 ; Youssef et al, 2021 ; Bashir et al, 2023 ; Urmi et al, 2023 ). In the present study, exogenously applied different levels of ALA through different modes were found effective in altering the CAT, SOD, and POD activities in favor of a better antioxidative defense mechanism.…”
Section: Discussioncontrasting
confidence: 58%
“…In the present study, activities of antioxidant enzymes such as CAT, SOD, and POD decreased under stress in both mungbean lines, but reports depict that up or down-regulation activities of antioxidant enzymes or plant genotype-specific and stress type-specific ( Wang et al, 2012 ; Rai, Morales & Aphalo, 2021 ; Youssef et al, 2021 ; Bashir et al, 2023 ; Urmi et al, 2023 ). In the present study, exogenously applied different levels of ALA through different modes were found effective in altering the CAT, SOD, and POD activities in favor of a better antioxidative defense mechanism.…”
Section: Discussioncontrasting
confidence: 58%
“…Proline is an amino acid synthesized from the phosphorylation of glutamate. Prolines have important functions in metabolic and physiological health [4].…”
Section: Introductionmentioning
confidence: 99%